The influence of the external magnetic field on energy losses of a charged particle in an electron gas - Khelemelia, O.V.; Kholodov, R.I. (Вопросы атомной науки и техники, 2017)
The influence of an external magnetic field and a temperature of an electron gas on energy losses of a charged massive particle is taken into account in the framework of quantum-field approach. The analytical expressions of real and imaginary parts of the dielectric susceptibility of the electron gas in the external magnetic field are obtained. Energy losses of the heavy charged particle in the electron gas in the magnetic field are numerical calculated. Results of the numerical calculations are verified by analytical expressions obtained in work [1]. В рамках квантово-полевого подхода учтены одновременно влияние и магнитного поля, и температуры электронного газа на энергетические потери тяжёлой заряженной частицы. Получены аналитические выражения для мнимой и реальной частей диэлектрической восприимчивости. Численно посчитаны энергетические потери тяжёлой заряженной частицы в электронном газе во внешнем магнитном поле. Результаты численного счёта верифицированы аналитическими результатами работы [1]. У рамках квантово-польового підходу одночасно врахований вплив як зовнішнього магнітного поля, так і температури електронного газу на енергетичні втрати важкої зарядженої частинки. Отримано аналітичні вирази для уявної та дійсної частин діелектричної сприйнятливості. Чисельно підраховані енергетичні втрати важкої зарядженої частинки в електронному газі в зовнішньому магнітному полі. Результати чисельного розрахунку добре узгоджуються із аналітичними результатами, отриманими в роботі [1].